Penerapan Balance Scorecard dalam Rangka Pengukuran Kinerja Perusahaan PT. Anugrah Iyan Pratama Makassar - Rahmita, Annisa Dwi; Alam, Syamsu; Bakri, Asriadi (FKIP, Universitas Banten Jaya, 2024)
Anugrah Iyan Pratama is a company that operates in the field of trade in health devices. PT. Anugrah Iyan Pratama needs to have a proper performance measurement system framework. Nowadays, the phenomenon that often occurs in PT. Anugrah Iyan Pratama is the inappropriate delivery of goods and payments that are often not on time due to something from the internal company. This phenomenon has a negative impact on long-term agility and success, so it needs to be based on a balanced scorecard in both performance and existing perspectives, such as a financial perspective consisting of return on investment (ROI), profit margin, and growth rate revenue, customer perspectives, internal business process perspectives, and growth and learning perspectives. This research aimed to test hypotheses, solved problems, and achieve goals.Based on the results of the research and discussions that have been outlined, the measurement of the financial perspective of PT. Anugrah Iyan Pratama Makassar showed excellent performance. This could be seen from ROI, profit margin, and growth in revenue. The measurement from the customer perspective of PT. Anugrah Iyan Pratama Makassar showed good performance. This could be seen from the excellent customer growth rate. Measuring from an internal business perspective that included company innovation and after-sales service showed good company performance because the company has strived to deliver better change in innovation. The evaluation of the performance achieved by PT. Anugrah Iyan Pratama Makassar as a whole was said to be good or satisfactory.